Loropetalum flavum (Hamamelidaceae), a new species from northern Vietnam - Averyanov, Leonid V.; Endress, Peter K.; Nguyen, Khang Sinh; Thai, Tran Huy; Maisak, Tatiana V.; Averyanova, Anna L.; Diep, Le Ngoc (Phytotaxa, 2018)
Loropetalum flavum (Hamamelidaceae) is described and illustrated as a new species from Bat Dai Son Mountains situated in the northern Vietnam. Recently discovered plant was observed as a typical element of the rich primary forest found on the highly eroded karstic limestone mountain formations allied to the border with China. The new species is characterized by arboreous habit; stellately indumentum of branchlets, leaves and flowers; axillary, capitate, 4–12-flowered inflorescences; yellow, sessile, actinomorphic, bisexual, 4–6-merous flowers with 2-whorled perianth and 2–8 fleshy disc lobes; stamens with conspicuous subulate connective protrusion; anthers with 2 rectangular 2-sporangiate thecae, each dehiscing by 2 valves and syncarpous gynoecium with 2-locular inferior ovary bearing 2 very short separate styles. A key to all known species of Loropetalum species is given and lectotype of L. lanceum is proposed.